Canine trypanosomiasis in Madre de Dios, Peru - Rojas Jaimes, Jesús Eduardo (2019)
The aim of this study was to report the presence of Trypanosoma sp in a blood smear from a dog in Madre de Dios, Peru. The animal was a resident of the district of Las Piedras and, when treated at a veterinary medical centre, was reported with a presumptive diagnosis of ehrlichiosis. A blood sample was collected, and the smear was stained with Wright, where trypomastigotes of Trypanosoma sp was observed. No cultures and molecular studies were performed because the sample was contaminated. This is the first report of canine trypanosomiasis in Madre de Dios.